Handbook of research on multidisciplinary approaches to literacy in the digital age - Taşkıran, Nurdan Öncel, 1960- (Advances in media, entertainment, and the arts (AMEA) book series., 2020)
"This book examines multidisciplinary approaches to literacy in the digital age"--Provided by publisher.